2019
DOI: 10.1002/ece3.5568
|View full text |Cite
|
Sign up to set email alerts
|

Host identity and phylogeny shape the foliar endophytic fungal assemblages of Ficus

Abstract: Foliar endophytic fungi (FEF) are diverse and ubiquitously associated with photosynthetic land plants. However, processes shaping FEF assemblages remain poorly understood. Previous studies have indicated that host identity and host habitat are contributing factors, but these factors are often difficult to disentangle. In this study, we studied FEF assemblages from plants grown in a botanical garden, enabling us to minimize the variation in abiotic environmental conditions and fungal dispersal capacity. FEF ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 77 publications
4
20
2
Order By: Relevance
“…The genotypic and phenotypic divergence among host species underlying phylogenetic relationships is complex and undoubtedly includes a wide array of traits that differentially influence colonization success of specific microbial taxa (Liu et al, 2019). For example, research on plant-pathogen interactions suggests that more closely related hosts share similar genetic pathways for cellular recognition of proteins and effector molecules during pathogen colonization and resistance (Barrett & Heil, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genotypic and phenotypic divergence among host species underlying phylogenetic relationships is complex and undoubtedly includes a wide array of traits that differentially influence colonization success of specific microbial taxa (Liu et al, 2019). For example, research on plant-pathogen interactions suggests that more closely related hosts share similar genetic pathways for cellular recognition of proteins and effector molecules during pathogen colonization and resistance (Barrett & Heil, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…and tropical forest grasses; Eusemann et al., 2016; Higgins et al., 2014). Similarly, one recent study found that FFE community structure was significantly related to host phylogeny among Ficus tree species in a mixed botanical garden (Liu et al., 2019), but no evidence for host phylogenetic drivers was found among families of trees in a tropical forest (Vincent et al., 2016). Thus, experiments that control for host phylogeny, but minimize broad regional differences in spatial and temporal sampling of host individuals, would be a strong test for the relative importance of host phylogeny versus local ecological conditions on the distribution of FFE.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The association we found between FEF beta diversity and host plant phylogenetic distance was the most important predictor in our GDM model. Previous studies of FEF have surveyed multiple host species and have found that host identity is commonly associated with fungal endophyte community composition (Liu, Zhao, Wang, & Chen, 2019;U'Ren et al, 2012;Vincent et al, 2016), even among closely related hosts (Christian et al, 2020), so our result was mostly expected. But unlike most previous studies that found host associations of FEF (although see Davis & Shaw, 2008), we used the phylogeny of host plants as an explanatory variable in place of their identity.…”
Section: Discussionmentioning
confidence: 54%
“…The plant and endophytes coevolved millions of years ago [1]. The composition of endophytic fungi is often diversified [2][3][4], and may vary as a function of host plant species [5,6], geographically distanced individuals of the same host species, and within the tissues or organs of a host plant [7]. In plant-endophyte mutualistic symbiosis, plants provide accommodation and diverse niches for endophytes [8].…”
Section: Introductionmentioning
confidence: 99%